A simple and robust model for prediction of liquid-loading onset in gas wells. (10th February 2021) - Zhang, Liehui; Luo, Chengcheng; Liu, Yonghui; Zhao, Yulong; Xie, Chunyu; Xie, Chuan
Accurate prediction of liquid loading is of great importance for production optimisation in gas wells. In this paper, the authors present a simple and accurate empirical model based on attached-film reversal for predicting liquid-loading onset in vertical and horizontal gas wells. Unlike established and complicated analytical models based on force balance, this model is developed from the empirical flooding equation by matching the experimental data from previous studies. Further, this model adopts the Belfroid angle-correction term for horizontal gas wells. Compared with the traditional entrained-droplet models, this model considers the effect of pipe diameter and liquid velocity. This study investigated the effect of pressure on the predicted critical gas velocity and scaled up low pressure by comparing some other analytical models. This model was also validated against the experimental data and field data. Results show that the presented model is capable of accurately predicting liquid-loading onset in gas wells. [Received: December 4, 2018; Accepted: December 13, 2019]